Design of bolted ball-cylinder joints under different load types. (October 2021) - Xiong, Zhe; Chen, Anyang; Chen, Lexian; Li, Yinglei; He, Jianian; Li, Lijuan; Zou, Xiaozhou; Qiu, Yu; Luo, Yunhai
Abstract: This paper presents an FE and theoretical study on bolted ball-cylinder (BBC) joint, which mainly consists of a circular tube welded to a solid hemisphere. As a new type of jointing system for non-purlin grid structures, BBC joints may be subjected to compressive, tensile and bending loads. A non-linear FE model was developed and its reliability was verified by the experimental results from existing literature. For a design purpose, the FE model was improved by removing the additional constraints that needed during the test and modifying the material constitutive model. Failure modes, typical load–displacement relationships and stress distributions were studied based on the FE simulations. Parametrical study was conducted to investigate the influence of key parameters, such as diameter, thickness, height of the circular tube, width and height of the tubular beam, on the structural behaviour of BBC joints under various loading scenarios. Finally, empirical formulas were proposed to predict the ultimate load capacity of BBC joints and the prediction agreed well with the FE results.